Method for recovering valuable material from lithium ion secondary battery
By performing heat treatment and graded magnetic separation processes on lithium-ion secondary batteries, the problem of low cobalt and nickel recovery grade in the prior art is solved, and high recovery rate and high grade metal recovery are achieved.
Patent Information
- Application Number
- CN202380052564.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-05-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the grade of cobalt and nickel recovery from lithium-ion secondary batteries is low and the recovery rate of copper cannot be effectively improved, and there are problems of low recovery rate and low grade.
After adopting the heat treatment process, cobalt, nickel and copper in the lithium ion secondary battery are separated and recovered through a series of grading and magnetic separation processes, including a first grading process, a crushing process, a second grading process and a magnetic separation process. Specific steps include: crushing after heat treatment, crushing after grading, re-classifying and magnetic separation to improve the recovery and grade of cobalt and nickel.
This method can effectively improve the recovery and grade of cobalt and nickel, and achieve high-grade metal recycling with high recovery, which is especially suitable for the recycling of battery packs or modules.
Smart Images

Figure CN119522502A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for recovering valuable substances from lithium ion secondary batteries. Background Art
[0002] Compared with conventional lead-acid batteries and nickel-cadmium secondary batteries, lithium-ion secondary batteries are lightweight, high-capacity, and high-electromotive force secondary batteries, and are used as secondary batteries for personal computers, electric vehicles, portable devices, and the like. For example, in the positive electrode of lithium-ion secondary batteries, valuable substances such as cobalt and nickel are used as lithium cobalt oxide (LiCoO2), ternary positive electrode materials (LiNi x Co y Mn z O2(x+y+z=1)) etc.
[0003] Since the use of lithium-ion secondary batteries is expected to expand in the future, from the perspective of resource recycling, it is expected to recover lithium and other valuables from defective products generated during the manufacturing process and lithium-ion secondary batteries that are discarded due to the life of the equipment and batteries used. When recovering lithium and other valuables from lithium-ion secondary batteries, it is important to separate and recover various metals or impurities used in lithium-ion secondary batteries from the perspective of increasing the value of the recovered materials.
[0004] As a method for recovering valuable substances such as cobalt, nickel, and copper from the crushed product of a heat-treated product of a lithium-ion secondary battery, a method for recovering valuable substances from a lithium-ion secondary battery has been proposed, for example, wherein the heat-treated product obtained by heat-treating the lithium-ion secondary battery is crushed, classified in two stages, and then subjected to multiple dry magnetic separation treatments (for example, refer to Patent Document 1).
[0005] In addition, the following valuable recovery method has been proposed, wherein the crushed product obtained by crushing the heat-treated product of a lithium-ion secondary battery is classified, the obtained fine particle product is immersed in water to prepare a water leaching slurry, and the aforementioned water leaching slurry is subjected to wet magnetic separation (for example, refer to Patent Document 2).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2020-61297
[0009] Patent Document 2: International Publication No. 2021 / 182451 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, in the valuable recovery method described in Patent Document 1, the cobalt (Co) and nickel (Ni) grades of the fine particles are low, and the grade of copper recovered as non-magnetic adsorbents cannot be improved. In addition, among the fine particles obtained in the second stage classification process, the Co and Ni that have been fined by the crushing process sometimes pass through the sieve, which makes it impossible to achieve the desired recovery of Co and Ni.
[0012] In the above-mentioned Patent Document 2, there is a problem that cobalt and nickel are sometimes included in the copper mixed in the fine-grained product, and therefore, high-grade cobalt and nickel cannot be recovered at a high recovery rate.
[0013] The present invention aims to solve various problems in the past and achieve the following objectives. That is, the present invention aims to provide a method for recovering valuables from lithium-ion secondary batteries, which can recover high-grade cobalt and nickel at a high recovery rate, and in particular, aims to recover high-grade cobalt and nickel at a high actual recovery rate even if a battery pack or module is used as an object.
[0014] Solutions for solving problems
[0015] As a method for solving the above-mentioned problem, the following is described.
[0016] <1> A method for recovering valuables from a lithium-ion secondary battery, comprising:
[0017] A heat treatment step of heat-treating the lithium-ion secondary battery to obtain a heat-treated product;
[0018] A first classification step of classifying the crushed product at a classification point of 600 μm or more and 2,400 μm or less to obtain a coarse particle product 1 and a fine particle product, wherein the crushed product is obtained by crushing the heat-treated product;
[0019] A pulverizing step of pulverizing the aforementioned fine-particle product to obtain a pulverized product;
[0020] a second classification step of classifying the pulverized product at at least one classification point smaller than the classification point in the first classification step and being 75 μm or more and 1,200 μm or less, thereby obtaining a coarse particle product 2 and a fine particle product 1; and
[0021] The magnetic separation step uses magnetic force to separate the fine particle product 1 obtained in the second classification step.
[0022] <2> According to the aforementioned <1> The method for recovering valuables from lithium-ion secondary batteries, wherein the pulverizing method in the aforementioned pulverizing step is a method for obtaining the following pulverized material: the pulverized material makes the mass ratio of the aforementioned particulate product 1 obtained in the aforementioned second classification step relative to the total mass of the aforementioned coarse particle product 2 and the aforementioned particulate product 1 become 85 mass% or more.
[0023] <3> According to the aforementioned <2> The method for recovering valuable substances from lithium-ion secondary batteries, wherein, in the aforementioned second classification step, when the mass ratio of the aforementioned particulate product 1 to the total mass of the aforementioned coarse particle product 2 and the aforementioned particulate product 1 is less than 85 mass %, the aforementioned coarse particle product 2 is returned to the aforementioned pulverization step.
[0024] <4> According to the aforementioned <1> ~ <2> The method for recovering valuable substances from a lithium ion secondary battery described in any one of the above, wherein copper is recovered from the coarse particle product 2.
[0025] <5> According to the aforementioned <1> The method for recovering valuables from lithium-ion secondary batteries, wherein in the second classification step, the pulverized material is classified at at least two classification points smaller than the classification points in the first classification step and being 75 μm or more and 1,200 μm or less, thereby obtaining a coarse particle product 3, a medium particle product and a microparticle product 2,
[0026] In the magnetic separation step, the particulate product 2 obtained in the second classification step is separated by magnetic force.
[0027] <6> According to the aforementioned <5> The method for recovering valuables from lithium-ion secondary batteries, wherein the pulverizing method in the aforementioned pulverizing step is a method for obtaining the following pulverized material: the pulverized material makes the mass ratio of the aforementioned particulate product 2 obtained in the aforementioned second classification step relative to the total mass of the aforementioned coarse-grained product 3, the aforementioned medium-sized product and the aforementioned particulate product 2 become 85% by mass or more.
[0028] <7> According to the aforementioned <6> The method for recovering valuable substances from lithium-ion secondary batteries, wherein, in the aforementioned second classification step, when the mass ratio of the aforementioned particulate product 2 to the total mass of the aforementioned coarse-grained product 3, the aforementioned medium-grained product and the aforementioned particulate product 2 is less than 85% by mass, the aforementioned medium-grained product is returned to the aforementioned pulverization step.
[0029] <8> According to the aforementioned <5> The method for recovering valuable substances from lithium-ion secondary batteries, wherein copper is recovered from the aforementioned coarse particle product 3.
[0030] <9> According to the aforementioned <1> ~ <2> The method for recovering valuable substances from a lithium ion secondary battery according to any one of the above aspects, wherein the pulverization step, the second classification step, and the magnetic separation step are all performed in a wet process.
[0031] Effects of the Invention
[0032] According to the present invention, various conventional problems can be solved, and a method for recovering valuable materials from lithium ion secondary batteries capable of recovering high-grade cobalt and nickel at a high recovery rate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a diagram showing an example of a process flow of the method for recovering valuable substances from a lithium ion secondary battery according to the present invention. DETAILED DESCRIPTION
[0034] (Method for recovering valuable materials from lithium-ion secondary batteries)
[0035] The method for recovering valuable substances from lithium ion secondary batteries of the present invention comprises a heat treatment step, a first classification step, a pulverization step, a second classification step and a magnetic separation step, and further comprises other steps as required.
[0036] The method for recovering valuable substances from a lithium ion secondary battery of the present invention is a method for recovering valuable substances from a lithium ion secondary battery as an object.
[0037] Here, valuables refer to valuable substances that can be traded without being discarded, and examples thereof include various metals, etc. As valuables in lithium-ion secondary batteries, examples thereof include copper (Cu), aluminum (Al), lithium (Li), cobalt (Co), nickel (Ni), iron (Fe), carbon (C), etc.
[0038] <Lithium-ion secondary battery>
[0039] There is no particular limitation on the lithium ion secondary battery used as the object, and it can be appropriately selected according to the purpose. Examples thereof include defective lithium ion secondary batteries produced in the manufacturing process of lithium ion secondary batteries, lithium ion secondary batteries discarded due to poor use of equipment, life of the equipment, etc., and used lithium ion secondary batteries discarded due to lifespan.
[0040] The shape, structure, size, and material of the lithium ion secondary battery are not particularly limited and can be appropriately selected depending on the purpose.
[0041] The shape of the lithium ion secondary battery is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include a laminated type, a cylindrical type, a button type, a coin type, a square type, and a flat type.
[0042] In addition, the form of the lithium-ion secondary battery is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include battery cells, battery modules, and battery packs. Here, a battery module refers to an object obtained by connecting and integrating a plurality of battery cells as unit batteries into a housing. A battery pack refers to an object obtained by integrating a plurality of battery modules into a housing. In addition, the battery pack may have a control regulator or a cooling device.
[0043] As a lithium ion secondary battery, for example, there can be listed a secondary battery having a positive electrode, a negative electrode, a separator, an electrolyte containing an electrolyte and an organic solvent, and an outer packaging container, wherein the outer packaging container is a battery case that contains the positive electrode, the negative electrode, the separator and the electrolyte. It should be noted that the lithium ion secondary battery can be in a state where the positive electrode and the negative electrode are detached.
[0044] -positive electrode-
[0045] The positive electrode is not particularly limited as long as it has a positive electrode active material containing at least one of cobalt and nickel, and can be appropriately selected depending on the purpose.
[0046] The shape of the positive electrode is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include a flat plate shape and a sheet shape.
[0047] --Positive electrode collector--
[0048] The shape, structure, size, material, etc. of the positive electrode current collector are not particularly limited and can be appropriately selected depending on the purpose.
[0049] Examples of the shape of the positive electrode current collector include a foil shape.
[0050] Examples of the material of the positive electrode current collector include stainless steel, nickel, aluminum, copper, titanium, and tantalum. Among these, aluminum is preferred.
[0051] The positive electrode material is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include positive electrode materials containing at least a lithium-containing positive electrode active material and, if necessary, a conductive agent and a binder resin.
[0052] The positive electrode active material is not particularly limited as long as it contains at least one of cobalt and nickel, and can be appropriately selected depending on the intended purpose.
[0053] Examples of positive electrode active materials include lithium manganese oxide (LiMn2O4) called LMO series, lithium cobalt oxide (LiCoO2) called LCO series, and LiNi3O4 called ternary series and NCM series. x Co y Mn zO2 (x+y+z=1), LiNi called NCA system x Co y Al z (x+y+z=1), lithium iron phosphate (LiFePO4), lithium cobalt-nickel oxide (LiCo 1 / 2 Ni 1 / 2 O2), lithium titanate (Li2TiO3), etc. In addition, these materials can be used in combination as the positive electrode active material.
[0054] The conductive agent is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include carbon black, graphite, carbon fibers, and metal carbides.
[0055] The binder resin is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include homopolymers or copolymers of vinylidene fluoride, tetrafluoroethylene, acrylonitrile, ethylene oxide, and the like, and styrene-butadiene rubber.
[0056] -negative electrode-
[0057] The negative electrode is not particularly limited as long as it has a negative electrode active material, and can be appropriately selected depending on the purpose.
[0058] The shape of the negative electrode is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include a flat plate shape and a sheet shape.
[0059] --Negative electrode collector--
[0060] The shape, structure, size, material, etc. of the negative electrode current collector are not particularly limited and can be appropriately selected depending on the purpose.
[0061] Examples of the shape of the negative electrode current collector include a foil shape.
[0062] Examples of the material of the negative electrode current collector include stainless steel, nickel, aluminum, copper, titanium, and tantalum, among which copper is preferred.
[0063] The negative electrode active material is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include carbon materials such as graphite and hard carbon, titanates, silicon, etc. In addition, these materials may be used in combination as the negative electrode active material.
[0064] The positive electrode current collector and the negative electrode current collector have a laminate structure, and the laminate is not particularly limited and can be appropriately selected depending on the intended purpose.
[0065] -Outer packaging container-
[0066] The material of the outer container (casing) of the lithium ion secondary battery is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include aluminum, iron, stainless steel, and resin (plastic).
[0067] Hereinafter, each step in the method for recovering valuable substances from a lithium ion secondary battery of the present invention will be described in detail.
[0068] <Heat treatment process>
[0069] The heat treatment step is a step of obtaining a heat-treated product by heat-treating the lithium-ion secondary battery. The heat-treated product (baked product) is a product obtained by heat-treating the lithium-ion secondary battery.
[0070] The method for performing the heat treatment in the heat treatment step is not particularly limited and can be appropriately selected depending on the purpose. For example, the heat treatment can be performed by heating the object in a known calcining furnace.
[0071] The calcining furnace is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include batch furnaces such as a rotary furnace, a fluidized bed furnace, a tunnel furnace, and a muffle furnace; a cupola furnace, and a layer-fired furnace.
[0072] The atmosphere used in the heat treatment is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include an air atmosphere, an inert atmosphere, a reducing atmosphere, and a low-oxygen atmosphere.
[0073] The atmospheric atmosphere (air atmosphere) refers to an atmosphere obtained by using an atmosphere (air) in which oxygen accounts for about 21% by volume and nitrogen accounts for about 78% by volume.
[0074] The inert atmosphere may be, for example, an atmosphere composed of nitrogen gas or argon gas.
[0075] The reducing atmosphere refers to an atmosphere containing CO, H 2 , H 2 S, SO 2 , etc. in an inert atmosphere such as nitrogen or argon.
[0076] The low-oxygen atmosphere refers to an atmosphere in which the oxygen concentration is 11 volume % or less.
[0077] The conditions for heat treating (heating) the object to be heat treated (heat treatment conditions) are not particularly limited as long as the constituent components of the object can be separated and crushed in the crushing / classification step described later, and can be appropriately selected according to the purpose.
[0078] Here, as heat treatment conditions, for example, heat treatment temperature, heat treatment time, etc. can be mentioned.
[0079] The heat treatment temperature refers to the temperature of the lithium ion secondary battery as the object to be heat treated. The heat treatment temperature can be measured by inserting a thermometer such as a thermocouple or a thermistor into the object to be heat treated.
[0080] As the temperature in the heat treatment (heat treatment temperature), it is preferably above 750°C, more preferably above 750°C and below 1,080°C, and particularly preferably above 750°C and below 900°C. By setting the heat treatment temperature to above 750°C, the lithium in Li(Ni / Co / Mn)O2 in the positive electrode active material and LiPF6 in the electrolyte can be made into lithium fluoride (LiF), lithium carbonate (Li2CO3), lithium oxide (Li2O) and other lithium-soluble substances in aqueous solution, which can be separated from impurities other than fluorine when the lithium is leached. In addition, by setting the heat treatment temperature to above 750°C, the cobalt oxide and nickel oxide contained in the positive electrode active material are reduced to the metal. In addition, these metals can be grown to a particle size that is easily magnetically attracted in the subsequent stage of magnetic separation. The higher the heat treatment temperature, the easier it is for this particle size growth to occur.
[0081] In addition, the outer container of the lithium ion secondary battery is preferably made of a material having a melting point higher than the heat treatment temperature.
[0082] When the outer packaging container of a lithium ion secondary battery uses a material having a melting point lower than the heat treatment temperature, it is preferred that the heat treatment be performed in a low oxygen atmosphere with an oxygen concentration of less than 11 volume % or at least in a manner such that the oxygen concentration inside the lithium ion secondary battery being calcined (especially the positive electrode collector and the negative electrode collector arranged in the outer packaging container of the lithium ion secondary battery) is less than 11 volume %.
[0083] In addition, as a method for achieving a low oxygen atmosphere, for example, the positive electrode or negative electrode of the lithium ion secondary battery can be placed in an oxygen-barrier container and heat-treated. The material of the oxygen-barrier container is not particularly limited as long as it is a material with a melting point above the heat treatment temperature, and can be appropriately selected according to the purpose. For example, when the heat treatment temperature is 800°C, iron, stainless steel, etc. having a higher melting point than the heat treatment temperature can be listed.
[0084] In order to release the gas pressure of the gas generated by the combustion of the electrolyte in the lithium ion secondary battery or the laminate, the oxygen barrier container is preferably provided with an opening. The opening area of the opening is preferably provided in a manner that is 12.5% or less relative to the surface area of the outer packaging container provided with the opening. The opening area of the opening is more preferably 6.3% or less relative to the surface area of the outer packaging container provided with the opening. There is no particular limitation on the shape, size, and formation location of the opening, and it can be appropriately selected according to the purpose.
[0085] As the heat treatment time of lithium ion secondary battery, there is no particular limitation, and it can be appropriately selected according to the purpose, preferably more than 1 minute and less than 5 hours, more preferably more than 1 minute and less than 3 hours. The heat treatment time is as long as the heat treatment time until the desired temperature of cobalt and nickel metallization is reached, and the holding time is as long as the time of metallization can be ensured. If the heat treatment time is within the preferred range, it is advantageous from the viewpoint of the cost consumed by the heat treatment.
[0086] Therefore, it is preferable to perform heat treatment at 750° C. or higher and 1,200° C. or lower for 1 hour or longer.
[0087] <First Classification Step (Crushing)>
[0088] The first classification step (crushing treatment) includes a treatment of obtaining a crushed product by crushing the heat-treated product.
[0089] The crushing treatment is not particularly limited as long as it can crush the heat-treated product (calcined product) to obtain a crushed product, and can be appropriately selected according to the purpose. In addition, the crushed product refers to a product obtained by crushing the heat-treated product.
[0090] As a crushing treatment, for example, the heat-treated object is preferably crushed by impact to obtain a crushed object. In addition, when the outer packaging container of the lithium ion secondary battery does not melt during the heat treatment, it is more preferred that: before the heat-treated object is impacted, the heat-treated object is pre-crushed by cutting the heat-treated object with a cutting machine.
[0091] As a method for crushing by impact, for example, a method of throwing the heat-treated object with a rotating striking plate to make it collide with the striking plate to impart an impact; a method of hitting the heat-treated object with a rotating beater, etc., can be performed using, for example, a hammer crusher. In addition, as a method for crushing by impact, it can be a method of hitting the heat-treated object with a ball such as ceramics, which can be performed using a ball mill. In addition, the crushing based on impact can also be performed using, for example, a double-shaft crusher with a short blade width and a short blade length that is crushed by compression.
[0092] Furthermore, as a method of crushing by impact, for example, a method of applying impact by hitting the heat-treated product with two rotating chains can be cited, and this can be carried out using, for example, a chain mill.
[0093] By crushing the heat-treated product by impact, the crushing of the positive electrode collector (e.g., aluminum (Al)) is promoted, but the negative electrode collector (e.g., copper (Cu)) whose shape does not change significantly exists in the form of foil, etc. Therefore, in the first classification step (crushing treatment), the negative electrode collector is only cut, so in the first classification step (classification treatment) described later, a crushed product in a state in which valuable substances (e.g., aluminum) derived from the positive electrode collector and valuable substances (e.g., copper (Cu)) derived from the negative electrode collector can be efficiently separated can be obtained.
[0094] The crushing time in the crushing treatment is not particularly limited and can be appropriately selected according to the purpose. The crushing time per 1 kg of lithium ion secondary batteries is preferably 1 second to 30 minutes, more preferably 2 seconds to 10 minutes, and particularly preferably 3 seconds to 5 minutes.
[0095] <First Classification Step (Classification Process)>
[0096] The first classification step (classification treatment) includes a treatment for obtaining a coarse particle product 1 and a fine particle product by classifying the crushed product obtained by crushing the above-mentioned heat-treated product at a classification point of 600 μm or more and 2,400 μm or less, preferably at a classification point of 850 μm or more and 1,700 μm.
[0097] The first classification step (classification treatment) is not particularly limited as long as the crushed product can be classified to obtain a coarse particle product 1 (oversize product) and a fine particle product (undersize product), and can be appropriately selected depending on the purpose.
[0098] The classification method is not particularly limited and can be appropriately selected according to the purpose, and can be performed using, for example, a vibrating screen, a multi-stage vibrating screen, a cyclone separator, a standard screen of JIS Z8801, a wet vibrating table, an air table, etc. By classification, copper (Cu), iron (Fe), etc. can be separated into coarse particles, and lithium, cobalt, nickel, or carbon can be concentrated into fine particles.
[0099] As the particle size for classification (classification point, mesh size of the sieve), from the viewpoint of separating copper (Cu), iron (Fe), aluminum (Al), etc. into coarse-grained products and concentrating carbon (C), lithium (Li), cobalt (Co), nickel (Ni), manganese (Mn), etc. into fine-grained products by classification, the classification point is set at 600 μm or more and 2,400 μm or less.
[0100] In addition, when a sieve is used as a classification method, the classification is performed by placing, for example, stainless steel balls or alumina balls on the sieve as a crushing promoter, so that small crushed materials attached to large crushed materials are separated from the large crushed materials, thereby more efficiently separating the large crushed materials from the small crushed materials. As a result, the grade of the recovered metal can be further improved.
[0101] As described above, the crushing process may be performed simultaneously with the classification process in the first classification process. For example, the crushing process may be performed as a crushing / classification process (crushing / classification) in which the heat-treated product obtained in the heat treatment process is crushed and the crushed product is classified into a coarse-grained product and a fine-grained product.
[0102] It should be noted that when the ratio of fine-grained products in the first classification step (classification treatment) is low, the coarse-grained product 1 may be returned to the step of crushing the heat-treated product. This can improve the recovery rate of valuable substances other than Fe and Cu.
[0103] <Crushing process>
[0104] The pulverization step is a step of pulverizing the fine particle product obtained in the first classification step (classification treatment) to obtain a pulverized product of a predetermined size. Specifically, the following (1) or (2) may be mentioned.
[0105] (1) The pulverization method in the pulverization step is a method for obtaining a pulverized product obtained in the second classification step (1) described later, wherein the mass ratio of the particulate product 1 to the total mass of the coarse particle product 2 and the particulate product 1 is 85 mass % or more. This can improve the recovery rate of cobalt (Co) and nickel (Ni) in the pulverized product.
[0106] When the mass ratio of the particulate product 1 obtained in the second classification step (1) described later to the total mass of the coarse particle product 2 and the particulate product 1 is less than 85 mass%, the coarse particle product 2 can be returned to the pulverizing step and repeatedly pulverized until the mass ratio of the above-mentioned particulate product 1 to the total mass of the coarse particle product 2 and the particulate product 1 becomes greater than 85 mass%.
[0107] (2) The pulverization method in the pulverization step is a method for obtaining a pulverized product obtained in the second classification step (2) described later, wherein the mass ratio of the fine particle product 2 to the total mass of the coarse particle product 3, the medium particle product and the fine particle product 2 is 85 mass % or more. This can improve the recovery rate of cobalt (Co) and nickel (Ni) in the pulverized product.
[0108] When the mass ratio of the particulate product 2 obtained in the second classification step (2) described later to the total mass of the coarse particle product 3, the medium particle product and the particulate product 2 is less than 85 mass%, the medium particle product can be returned to the crushing step and the crushing is repeated until the mass ratio of the particulate product 2 to the total mass of the coarse particle product 3, the medium particle product and the particulate product 2 becomes greater than 85 mass%.
[0109] The pulverizing step is not particularly limited as long as the pulverized material can be pulverized to the aforementioned size, and can be appropriately selected according to the purpose. For example, a media stirring type pulverizer (grinder, bead mill, tower mill) using media such as iron balls, a roller mill, a jet mill, a high-speed rotary pulverizer (hammer mill, pin mill), a container-driven mill (rotary mill, vibration mill, planetary mill), etc. can be used.
[0110] The pulverization process can be either a wet process or a dry process, and can be appropriately selected according to the purpose, preferably carried out by a wet process (wet pulverization process). By using a wet process, the reduction in the actual yield of Co and Ni caused by the dust generation in each process can be suppressed, and there is no need to prevent the dust from scattering to the surrounding atmosphere. When performing wet pulverization, it is preferred to perform a slurrying process of obtaining a slurry-like liquid (fine particle product slurry) by immersing the fine particle product obtained after the first classification process in water.
[0111] The slurrying step is not particularly limited as long as it is a step in which the fine particles recovered in the crushing / classification step are immersed in water (soaked or thrown into water) to disperse the fine particles in water to obtain a slurry (suspension), and can be appropriately selected depending on the purpose.
[0112] The dispersion medium for slurrying the fine particle product is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include pure water such as industrial water, tap water, ion exchange water, ultrafiltration water, reverse osmosis water, and distilled water, and ultrapure water.
[0113] Here, the leaching method in the water leaching step is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include a method of simply putting the fine-particle product into water in advance; a method of putting the fine-particle product into water and stirring it; a method of putting the fine-particle product into water and slowly stirring it while irradiating ultrasonic waves; a method of adding water to the fine-particle product, etc. As the leaching method, for example, a method of putting the fine-particle product into water and stirring it is preferred, and a method of putting the fine-particle product into water and slowly stirring it while irradiating ultrasonic waves is more preferred.
[0114] The solid-liquid ratio (mass ratio of fine particle product to water) in the water leaching process is not particularly limited and can be appropriately selected according to the purpose. It is preferably above 1% and below 40%, and particularly preferably above 5% and below 20%. If the solid-liquid ratio is less than 1%, the cobalt and nickel originally recovered in the form of magnetically adsorbed materials are not recovered by the magnetic separator, but are lost to the non-magnetically adsorbed materials, and the recovery rate of cobalt / nickel is likely to decrease. If the solid-liquid ratio exceeds 40%, the impurities entrapped in the magnetically adsorbed materials may increase, and the grades of cobalt and nickel may decrease.
[0115] The stirring speed of the water in the water leaching step is not particularly limited and may be appropriately selected depending on the purpose, and may be, for example, 200 rpm.
[0116] The leaching time in the water leaching step is not particularly limited and may be appropriately selected depending on the intended purpose, and may be, for example, 1 hour.
[0117] <Second Classification Step>
[0118] The second classification step is a step of classifying the pulverized product obtained in the pulverization step at at least one classification point, and specifically, the following (1) or (2) may be mentioned.
[0119] (1) The second classification step is a step of obtaining a coarse particle product 2 and a fine particle product 1 by classifying the pulverized material obtained in the pulverization step (1) at a classification point smaller than the classification point in the first classification step and being 75 μm or more and 1,200 μm or less.
[0120] When the mass ratio of the particulate product 1 obtained in the second classification step of the aforementioned (1) to the total mass of the coarse particle product 2 and the particulate product 1 is less than 85 mass%, the coarse particle product 2 can be returned to the aforementioned pulverization step and repeatedly pulverized until the mass ratio of the particulate product 1 to the total mass of the coarse particle product 2 and the particulate product 1 becomes greater than 85 mass%.
[0121] For example, when the pulverized product obtained in the pulverization step (1) is subjected to the second classification step using a standard sieve of JIS Z8801 with a classification point of 500 μm, the product on the sieve of the standard sieve with a classification point of 500 μm is a coarse particle product 2, and the product under the sieve is a fine particle product 1. It should be noted that copper can be concentrated and recovered from the coarse particle product 2.
[0122] (2) The second classification step is a step of obtaining a coarse particle product 3, a medium particle product and a fine particle product 2 by classifying the pulverized material obtained in the above-mentioned pulverization step (2) at at least two classification points which are smaller than the classification points in the first classification step and are 75 μm or more and 1,200 μm or less.
[0123] When the mass ratio of the particulate product 2 obtained in the second classification step (2) above to the total mass of the coarse particle product 3, the medium particle product and the particulate product 2 is less than 85 mass%, the medium particle product can be returned to the above-mentioned pulverization step and the pulverization is repeatedly performed until the mass ratio of the particulate product 2 to the total mass of the coarse particle product 3, the medium particle product and the particulate product 2 becomes greater than 85 mass%.
[0124] The second classification step (2) is performed at least at two classification points.
[0125] For example, the pulverized material can be classified at the same time with a first classification point of 300 μm or more and less than 1,200 μm and a second classification point smaller than the first classification point and 75 μm or more and less than 600 μm. Thus, a coarse particle product 3 larger than the first classification point, a medium particle product smaller than the first classification point and larger than the second classification point, and a fine particle product 2 smaller than the second classification point can be obtained.
[0126] In addition, for example, for the pulverized product obtained in the pulverization step (2), the second classification step can be divided into two steps using two standard sieves of JIS Z8801 with classification points of 500 μm and 250 μm. In this case, by placing the pulverized product on the standard sieve with the classification point of 500 μm, a coarse particle product 3 is obtained as an oversize product of more than 500 μm, and an intermediate product (including a medium particle product and a microgranular product 2) is obtained as an undersize product. Then, by placing the intermediate product on the standard sieve with the classification point of 250 μm, a medium particle product is obtained as an oversize product of more than 250 μm, and a microgranular product 2 is obtained as an undersize product of less than 250 μm.
[0127] It should be noted that copper can be concentrated and recovered from the coarse particle product 3.
[0128] The classification point used in the second classification step is smaller than the classification point in the first classification step and is 75 μm or more and 1,200 μm or less, preferably 106 μm or more and 850 μm or less, and particularly preferably 150 μm or more and 600 μm or less. If the classification point exceeds 1,200 μm, the mixing of copper into the micro-particle product 1 or micro-particle product 2 may increase, thereby reducing the grade of cobalt and nickel. If the classification point is less than 75 μm, the pulverization energy for recovering cobalt and nickel into the micro-particle product 1 or micro-particle product 2 may be too large.
[0129] The second classification step is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include a vibrating screen, a multi-stage vibrating screen, a cyclone separator, a JIS Z8801 standard screen, a wet vibrating table, and a pneumatic table.
[0130] The second classification step is not particularly limited and can be appropriately selected according to the purpose, and is preferably performed in a wet manner. When performing wet classification, the pulverized material slurry obtained in the wet pulverization step can be directly supplied, or water can be added to the pulverized material slurry for dilution to adjust the solid-liquid ratio.
[0131] <Magnetic separation process>
[0132] The magnetic separation step is a step of separating the fine-particle product 1 or the fine-particle product 2 obtained in the second classification step by magnetic force. It may be either dry magnetic separation or wet magnetic separation, but wet magnetic separation is preferred from the following viewpoints.
[0133] When the particulate product 1 or particulate product 2 obtained in the second classification step is subjected to magnetic separation, in the case of performing magnetic separation by, for example, dry separation, sometimes the particles aggregate due to the attached moisture between the particles, and the metal particles derived from the negative electrode collector and more than 10% of the negative electrode active material particles contained in the particulate product 1 or particulate product 2 cannot be fully separated from the cobalt and nickel particles. Therefore, in the present invention, it is preferred to perform wet magnetic separation to separate the material derived from the negative electrode active material and the metal derived from the negative electrode collector into a non-magnetic adsorbent slurry, and recover cobalt and nickel in the form of magnetic adsorbents.
[0134] In the present invention, the cobalt and nickel of the magnetically adsorbed material have high grades and low impurity grades, and therefore can be used as smelting raw materials of cobalt and nickel as they are. In addition, the cost of purification used as raw materials (such as cobalt sulfate, nickel sulfate, etc.) for obtaining manufacturing materials for secondary batteries can be reduced.
[0135] The magnetic separation step is a step of separating the fine-particle product 1 or the fine-particle product 2 obtained in the second classification step into magnetically adsorbed matter and non-magnetically adsorbed matter.
[0136] Here, the magnetically adsorbed object refers to a substance that can be adsorbed to the side of a magnetic source (magnetic field) by generating an attractive force with the magnetic source (e.g., a magnet, an electromagnet, etc.) using the magnetic force generated by the magnetic source. Examples of magnetically adsorbed objects include ferromagnetic metals. Examples of ferromagnetic metals include iron (Fe), nickel (Ni), and cobalt (Co).
[0137] Non-magnetic adsorbents refer to substances that are not adsorbed to the magnetic source side by the magnetic force generated by the magnetic source. There are no particular limitations on the non-magnetic adsorbents, and they can be selected according to the purpose. In addition, as metal non-magnetic adsorbents, for example, paramagnetic or semi-magnetic metals can be listed. As paramagnetic or semi-magnetic metals, for example, aluminum (Al), manganese (Mn), gold (Au), silver (Ag), copper (Cu), etc. can be listed.
[0138] The magnetic separation step is not particularly limited, and can be performed using a known magnetic separator (magnetic separator) or the like, and examples thereof include a cylindrical magnetic separator and a high-gradient magnetic separator.
[0139] The magnetic field strength of the magnetic separator is not particularly limited and can be appropriately selected according to the purpose. It is preferably 1,000G or more and 40,000G or less, more preferably 3,000G or more and 30,000G or less, and particularly preferably 6,000G or more and 20,000G or less. If the magnetic field strength is less than 1,000G, it is not easy to magnetically absorb cobalt and nickel particles, and the recovery rate of cobalt and nickel in the magnetically adsorbed material is likely to decrease. If the magnetic field strength exceeds 40,000G, the recovery rate of impurities other than cobalt and nickel in the magnetically adsorbed material increases, and the cobalt and nickel grades in the magnetically adsorbed material decrease.
[0140] The magnetic separation process can be performed multiple times (multi-stage). For example, by performing a second stage of magnetic separation (fine separation) on the magnetically adsorbed material recovered in the first stage of the magnetic separation process, the impurities trapped in the cobalt and nickel particles due to the first stage of the magnetic separation process are separated again, thereby improving the cobalt (Co) and nickel grades of the magnetically adsorbed material.
[0141] In addition, by subjecting the non-magnetic adsorbents recovered in the first stage magnetic separation process to the second stage magnetic separation (cleaning separation), the cobalt and nickel lost to the non-magnetic adsorbents can be recovered in the form of magnetic adsorbents, thereby improving the overall actual yield of cobalt and nickel. Cobalt and nickel particles have a larger particle size than carbon, which is the main impurity. Therefore, by preliminarily recovering relatively coarse cobalt and nickel particles by the first stage magnetic separation, the relatively fine cobalt and nickel that are not recovered by the first stage magnetic separation have a particle size similar to that of carbon, which is an impurity. When the cobalt and nickel particles are recovered by the second stage magnetic separation, the inclusion of impurities can be reduced, and a better magnetic separation effect can be obtained.
[0142] In the wet magnetic separation, the undersize product slurry obtained by the wet second classification step can be directly supplied, or the undersize product slurry can be concentrated or diluted by solid-liquid separation such as sedimentation separation to adjust the solid-liquid ratio. In addition, water can be added to the undersize product slurry to dilute it to adjust the solid-liquid ratio.
[0143] The solid-to-liquid ratio (mass ratio of particulate product 1 or particulate product 2 to water) of the slurry supplied to the wet magnetic separation is not particularly limited and can be appropriately selected according to the purpose, preferably being 5% or more and 67% or less, and more preferably being 10% or more and 40% or less. If the solid-to-liquid ratio is less than 5%, the recovery rate of cobalt and nickel as magnetically adsorbed substances in the wet magnetic separator is sometimes reduced. If the solid-to-liquid ratio exceeds 67%, problems such as pump blockage are sometimes likely to occur when the slurry is supplied, and the separation effect of cobalt and nickel (magnetically adsorbed substances) from non-magnetically adsorbed substances such as carbon is reduced.
[0144] The method for supplying the slurry is not particularly limited and may be appropriately selected depending on the purpose. The slurry may be supplied by a pump while stirring the slurry in the tank.
[0145] The magnetically adsorbed material recovered by wet magnetic separation contains moisture. Therefore, it can be separated into solid and liquid using filter paper, filter press or centrifuge, air-dried, or heated and dried using a dryer to remove moisture.
[0146] The non-magnetic adsorbent slurry contains lithium aluminate (LiAlO2), carbon, copper (material that cannot be recovered into the coarse particle product) and lithium (water soluble).
[0147] By adding acid to the non-magnetic adsorbent slurry, the lithium in the lithium aluminate contained in the non-magnetic adsorbent is acid-leached (acid leaching process), and then solid-liquid separation is performed, so that the solid-liquid separation can be carried out into a filtrate (acid leaching solution) and a filter residue (carbon concentrate).
[0148] Calcium hydroxide (Ca(OH)2; slaked lime) can be added to the acid leaching solution for neutralization (neutralization process), and solid-liquid separation can be performed by filtering with a filter press to separate the solution into a liquid containing lithium and a solid containing impurities such as fluorine or aluminum. Sodium carbonate (Na2CO3) can be added to the neutralized liquid, and solid-liquid separation can be performed by filtering with a filter press to separate the calcium dissolved in the neutralized liquid into the solid in the form of calcium carbonate. The liquid containing lithium can be heated to evaporate and concentrate the solution, and the lithium can be recovered in the form of lithium carbonate (Li2CO3).
[0149] <Other Processes>
[0150] The other steps are not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include a liquid purification step, a drying step, and a purification step.
[0151] <Example of Implementation>
[0152] Here, an example of an embodiment of the method for recovering valuable substances from a lithium ion secondary battery according to the present invention will be described with reference to the drawings. Figure 1 This is a diagram showing an example of a process flow in an embodiment of the method for recovering valuable substances from a lithium ion secondary battery according to the present invention.
[0153] First, a lithium ion secondary battery (LIB; Lithium Ion Battery) is heat-treated (heat-treatment step) to obtain a heat-treated product.
[0154] Next, the crushed product obtained by crushing the heat-treated product is classified at a classification point of 1,200 μm to obtain a coarse particle product and a fine particle product. Here, copper (Cu), iron (Fe), etc. can be separated from the coarse particle product.
[0155] Next, the fine product is immersed in water to obtain a fine product slurry. At this time, while lithium (lithium oxide or lithium carbonate) is leached into the water, a residue containing nickel (Ni), cobalt (Co), and manganese (Mn) is formed in the fine product slurry.
[0156] Next, the obtained fine particle product slurry is wet-milled to obtain a milled product slurry.
[0157] Next, the obtained pulverized product slurry is wet classified at a classification point of 75 μm or more and 1,200 μm or less to obtain a coarse particle product slurry and a fine particle product slurry. The obtained coarse particle product slurry is returned to the pulverization step, and the pulverization step is repeated until 85% by mass or more of the pulverized product slurry is distributed to the fine particle product slurry.
[0158] Next, the obtained fine particle product slurry is subjected to wet magnetic separation to be separated into magnetically adsorbed matter and non-magnetically adsorbed matter slurry. The magnetically adsorbed matter contains nickel (Ni) and cobalt (Co).
[0159] The non-magnetic adsorbent slurry contains lithium aluminate (LiAlO2), carbon, copper (material that cannot be recovered into the coarse particle product) and lithium (water soluble).
[0160] Next, acid is added to the non-magnetic adsorbent slurry to acid-leach lithium in lithium aluminate contained in the non-magnetic adsorbent (acid leaching step), followed by solid-liquid separation, thereby separating the solid and liquid into a filtrate (acid leaching solution) and a filtration residue (carbon concentrate).
[0161] Example
[0162] Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples at all.
[0163] (Example 1)
[0164] -Heat treatment process-
[0165] For the battery pack (about 300 kg) of lithium-ion secondary batteries to be processed, an intermittent combustion furnace of Eco-System Akita was used as a heat treatment device. Heat treatment was carried out under the conditions of a heat treatment temperature of 800°C (it took 15 minutes to raise the temperature from 20°C to 800°C and then maintained for 2 hours) and an atmospheric atmosphere to obtain a heat-treated product.
[0166] - Crushing process -
[0167] Next, the heat-treated lithium ion secondary battery was crushed using a chain mill (Cross Flow Shredder S-1000, manufactured by Sato Iron Works Co., Ltd.) as a crushing device at 50 Hz (chain tip speed of about 60 m / sec) and a residence time of 50 sec to obtain crushed lithium ion secondary batteries.
[0168] Next, the crushed lithium ion secondary battery was sieved using a sieve with a mesh size of 1.2 mm (diameter 200 mm, manufactured by TOKYO SCREEN Co., Ltd.), and the 1.2 mm oversize product (coarse particle product) and undersize product (fine particle product) were collected after sieving.
[0169] -Slurrying process-
[0170] 62.5 kg of the obtained fine particle product was immersed in 250 L of water, and lithium was leached into the water under the conditions of a solid-liquid ratio of 25%, a stirring speed of 400 rpm, and a leaching time of 1 hour to obtain a fine particle product slurry.
[0171] -Wet pulverization process-
[0172] The obtained fine particle product slurry and 10 kg of pulverizing media (iron balls) were fed into a media stirring pulverizer (tower mill NE008, manufactured by Nippon Eirich Co., Ltd.) in 20 portions and wet pulverized for 30 minutes at a rotation speed of 716 rpm (circumferential speed of 3 m / sec) per portion.
[0173] -Wet Classification Process-
[0174] Next, the obtained fine particle product slurry was wet classified using two standard sieves of JIS Z8801 having classification points (mesh openings) of 500 μm and 250 μm.
[0175] The product on the sieve with a classification point of 500 μm is a coarse particle product 3, the product on the sieve with a classification point of 250 μm is a medium particle product, and the product under the sieve with a classification point of 250 μm is a fine particle product 2.
[0176] In order to make the mass ratio of the fine particle product 2 to the total mass of the coarse particle product 3, the medium particle product and the fine particle product 2 be 85 mass % or more, the medium particle product is returned to the pulverization step and pulverized repeatedly. The final mass ratio is: 8% for the coarse particle product 3, 4% for the medium particle product, and 88% for the fine particle product 2.
[0177] -Wet magnetic separation process-
[0178] Next, the slurry containing the fine particle product 2 was subjected to wet magnetic separation at a magnetic flux density of 6,000 G using a cylindrical magnetic separator (product name: REX WD Φ15×12, manufactured by Eriez Magnetics) to recover magnetically adsorbed matter (containing water) and non-magnetically adsorbed matter slurry.
[0179] Next, the obtained magnetically adsorbed product (containing water) was filtered at a pressure of 0.6 MPa using a filter press using a filter cloth (product name: PP934K, manufactured by Nakao Filter Industry Co., Ltd.) to obtain a magnetically adsorbed product (dehydrated). The obtained magnetically adsorbed product (dehydrated) was dried at 105° C. for 24 hours using a dryer (product name: DRM620DD, manufactured by Advantec Toyo Co., Ltd.) to obtain a magnetically adsorbed product.
[0180] <Determination of grade and recovery rate>
[0181] After drying at 105°C for 1 hour, the mass of the magnetically adsorbed material was measured using an electromagnetic scale (product name: GX-8K, manufactured by A&D Corporation). The magnetically adsorbed material was then heated and dissolved in aqua regia and analyzed using a high-frequency inductively coupled plasma emission spectrometer (SPECTROGREEN FMX46, manufactured by Hitachi High-Tech Science) to determine the grades of cobalt and nickel and the recovery rates of cobalt and nickel.
[0182] In addition, the oversize product (coarse particle product 3) with a classification point of 500 μm obtained in the wet classification step was analyzed using a high-frequency inductively coupled plasma emission spectrometer (SPECTROGREEN FMX46, manufactured by Hitachi High-Tech Science Co., Ltd.) to determine the copper grade of the obtained coarse particle product 3.
[0183] <Results>
[0184] In Example 1, a magnetically adsorbed product having a cobalt grade of 22% and a nickel grade of 21% was obtained, and the recovery rate of cobalt was 91% and the recovery rate of nickel was 88%. In addition, the copper grade of the coarse particle product 3 (the product on the sieve with a classification point of 500 μm) in the wet classification process was 43%.
[0185] (Comparative Example 1)
[0186] In Example 1, the fine particle product under the 1.2 mm sieve is not wet-crushed, but is classified using a wet vibrating screen with standard sieves having classification points of 500 μm and 250 μm, and the product under the sieve with a classification point of 250 μm is subjected to wet magnetic separation. Except for this, the same operations as in Example 1 are performed to obtain the magnetically adsorbed material of Comparative Example 1.
[0187] <Results>
[0188] The magnetically adsorbed material and the sieve-surface product with a classification point of 500 μm in the wet classification process were measured in the same manner as in Example 1. As a result, a magnetically adsorbed material with a cobalt grade of 16% and a nickel grade of 17% was obtained, and the recovery rates of cobalt and nickel were 42% and 44%. In addition, the copper grade of the sieve-surface product with a classification point of 500 μm in the wet classification process was 13%.
[0189] (Comparative Example 2)
[0190] The fine particle product recovered by the method described in Example 1 was used as the undersize product of the first-stage classification step described in Example 1 of JP-A-2020-61297, and the subsequent steps were repeated to obtain the magnetically adsorbed product of Comparative Example 2.
[0191] <Results>
[0192] The obtained magnetic adsorbent was measured in the same manner as in Example 1. As a result, a magnetic adsorbent with a cobalt grade of 10% and a nickel grade of 9% was obtained, with a cobalt recovery rate of 32% and a nickel recovery rate of 31%. In the fine-grained product (the product under the sieve with a mesh size of 0.3 mm) in Japanese Patent Gazette No. 2020-61297, the cobalt loss was 17% and the nickel loss was 18%. This is believed to be because: since the lithium-ion secondary battery of the battery pack size was heat treated, a deviation in the heat treatment temperature occurred in the battery pack, and cobalt and nickel where sufficient particle growth did not occur were locally present.
[0193] In addition, the intermediate product was magnetically separated in two stages, but in the first stage magnetic separation and the second stage magnetic separation of non-magnetic adsorbents, cobalt loss was 33% and nickel loss was 35%, and cobalt and nickel could not be fully recovered into the magnetic adsorbent. This is believed to be because the cobalt and nickel particles that did not grow sufficiently were not magnetically attracted to the hand-held magnet with a magnetic force of 1500G.
[0194] This international application claims priority based on Japanese Patent Application No. 2022-112516 filed on July 13, 2022, and all contents of Japanese Patent Application No. 2022-112516 are incorporated herein by reference.
Claims
1. A method for recovering valuables from a lithium-ion secondary battery, characterized in that: include: A heat treatment step of heat-treating the lithium-ion secondary battery to obtain a heat-treated product; a first classification step of classifying the crushed product at a classification point of 600 μm or more and 2,400 μm or less to obtain a coarse particle product 1 and a fine particle product, wherein the crushed product is obtained by crushing the heat-treated product; A pulverizing step of pulverizing the fine-particle product to obtain a pulverized product; a second classification step of classifying the pulverized product at at least one classification point smaller than the classification point in the first classification step and being 75 μm or more and 1,200 μm or less, thereby obtaining a coarse particle product 2 and a fine particle product 1; as well as The magnetic separation step uses magnetic force to separate the particulate product 1 obtained in the second classification step.
2. The method for recovering valuables from a lithium ion secondary battery according to claim 1, wherein: The pulverization method in the pulverization step is a method for obtaining a pulverized product in which the mass ratio of the fine particle product 1 obtained in the second classification step to the total mass of the coarse particle product 2 and the fine particle product 1 is 85 mass % or more.
3. The method for recovering valuables from a lithium ion secondary battery according to claim 2, wherein: In the second classification step, when the mass ratio of the fine particle product 1 to the total mass of the coarse particle product 2 and the fine particle product 1 is less than 85 mass %, the coarse particle product 2 is returned to the pulverization step.
4. The method for recovering valuable substances from a lithium ion secondary battery according to claim 1 or 2, wherein: Copper is recovered from the coarse product 2 .
5. The method for recovering valuable substances from a lithium ion secondary battery according to claim 1, wherein: In the second classification step, the pulverized product is classified at at least two classification points smaller than the classification point in the first classification step and being 75 μm or more and 1,200 μm or less, thereby obtaining a coarse particle product 3, a medium particle product, and a fine particle product 2, In the magnetic separation step, the fine particle product 2 obtained in the second classification step is separated by magnetic force.
6. The method for recovering valuable substances from a lithium ion secondary battery according to claim 5, wherein: The pulverization method in the pulverization step is a method for obtaining a pulverized product in which the mass ratio of the fine particle product 2 obtained in the second classification step to the total mass of the coarse particle product 3, the medium particle product, and the fine particle product 2 is 85 mass % or more.
7. The method for recovering valuable substances from a lithium ion secondary battery according to claim 6, wherein: In the second classification step, when the mass ratio of the fine particle product 2 to the total mass of the coarse particle product 3, the medium particle product and the fine particle product 2 is less than 85 mass %, the medium particle product is returned to the pulverization step.
8. The method for recovering valuable substances from a lithium ion secondary battery according to claim 5, wherein: Copper is recovered from the coarse product 3 .
9. The method for recovering valuable substances from a lithium ion secondary battery according to claim 1 or 2, wherein: The pulverizing step, the second classification step, and the magnetic separation step are all performed in a wet process.
Citation Information
Patent Citations
Method of recovering valuable material from lithium ion secondary battery
JP2020061297A
mask
JP2022112516A
Method for recovering valuable substance
WO2021182451A1